Serial vs. Parallel Processing: Sometimes They Look like Tweedledum and Tweedledee but they can (and Should) be Distinguished - Townsend, James T. (Psychological Science, 1990)
A number of important models of information processing depend on whether processing is serial or parallel. However, many of the studies purporting to settle the case use weak experimental paradigms or results to draw conclusions. A brief history of the issue is given along with examples from the literature. Then a number of promising methods are presented from a variety of sources with some discussion of their potential. A brief discussion of the topic with regard to overall issues of model testing and applications concludes the paper.